Islamic Gratitude Psychoeducational Group Model to Increase Student Resilience - Umriana, Anila; Sugiharto, Dwi Yuwono Puji; Mulawarman; Ashari Mahfud (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2025)
One aspect of university quality assurance is providing guidance and counseling services for students. Students are vulnerable to various problems while undergoing education in higher education. Resilience is one of the characters that is important for students to be able to survive and recover from various difficult situations and problems experienced. To increase resilience, appropriate treatment is needed along with a model as a reference. This study aims to develop a psychoeducational group service model based on Islamic Gratitude to improve student resilience. The research method uses Borg and Gall developmental research until the expert and practitioner validation stage and produces a prototype. The results of the research are the Islamic Gratitude Psychoeducational Group Model to Increase Student Resilience which integrates the stages of gratitude intervention developed by Bohlmajer and the values of gratitude in Islam which include syukr bil qalb, syukr bil lisan, and syukr bil hal, and contains the values of Iman, Islam, and Ihsan. Expert validation of the model shows that the model is feasible and can be used. Further research can conduct small group tests/experimental tests to measure the effectiveness of the developed model